MAKNA KEPEMIMPINAN TRANSFORMASIONAL BAGI GURU: STUDI FENOMENOLOGI PADA SMP NEGERI 2 DANAU PARIS KABUPATEN ACEH SINGKIL - Yessy Marlin; Yulfianti Yulfianti; Nurhizrah Gistituati; Rusdinal Rusdinal; Nellitawati Nellitawati (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Transformational Leadership is a person's skill in influencing others so that they are willing to follow what their leader wants. In the educational context, an educator, known as a teacher, is a profession crucial for implementing the best education. This study aims to understand how teachers interpret and give meaning to transformational leadership styles within the context of a phenomenological study. Data were collected through in-depth interviews using a qualitative Max Van Manen hermeneutics approach with three themes and subthemes: motivation, inspiration, and intellectual stimulation. Teachers were selected and described in a measurable manner to explore their experiences and emerging meanings. The results indicate that transformational leadership provides motivation, inspiration, and intellectual stimulation that encourage teacher performance in achieving achievement, while strengthening interpersonal relationships and professionalism. This study emphasizes the importance of implementing transformational policies in improving the performance and quality of education in schools. These findings empower the development of principals' leadership competencies to create a more productive learning environment and support teacher development.